Down syndrome: systematic review of the prevalence and nature of presentation of unipolar depression. Issue 4 (6th July 2015) - Walton, Catherine; Kerr, Mike
Abstract : Purpose: – The purpose of this paper is to assess the prevalence and nature of presentation of unipolar depression in individuals with Down syndrome (DS). Design/methodology/approach: – The PRISMA (2009) checklist for systematic review was followed where possible. Findings: – Eight studies were included in the qualitative synthesis from a total of 634 records identified. The quality of the studies was then assessed: the studies all scored either 5 or 6 out of 6. The incidence of depression ranged between studies from 5 to 13 per cent. It was found that depression is more common in DS than the general intellectual disability population; this on a background of mental ill health of all causes being less common in DS. It was suggested that, excluding organic disorders, depression is the most common psychiatric problem in DS. In terms of the nature of depression, the evidence was less clear. Various "vegetative" and biological symptoms were observed, with no fixed pattern. There was evidence for withdrawal symptoms and psychosis. Research limitations/implications: – The small number of studies included in this review, and their heterogeneity, highlights the need for further original research in this field. Practical implications: – An increased awareness of the frequency of depression in individuals with DS will aid in a timely diagnosis, therefore reduce psychiatric morbidity. Clinicians should be aware of the varied presentation, with no clear clinical picture, in order to maintain a high index of suspicion in an individual presenting with "atypical" symptoms. Originality/value: – This review has provided preliminary evidence that depression may be the most commonly experienced psychiatric disorder in DS.